PENGARUH PEMBERIAN KOMPRES BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH PADA BALITA DEMAM DI PUSKESMAS KEMBARAN 1 - Rachma Kailasari ,; Etika Dewi Cahyaningrum ,; Roro Lintang Suryani , (Jurnal Cakrawala Ilmiah, 2023)
Fever in toddlers is one sign of toddlers experiencing infectious diseases. Fever that is not handled properly can cause negative impacts such as seizures, one of the treatments for fever can be done with non-pharmacological treatment. Non-pharmacological treatment can be done using traditional medicines such as red onion (Allium Cepa var. ascalonicum). The purpose of the study was to determine the effect of giving red onion compresses on reducing body temperature in toddlers with fever. Work Area of the Kembaran Health Center 1. The design was a pre-experimental design with the type of one group pretest-posttest design. The sample in this study were toddlers who had a fever at the Kembaran I Health Center 15 respondents with purposive sampling technique. The instrument used an observation sheet and a thermometer. Data analysis used paired t-test. The results showed that the average body temperature in toddlers with fever before giving red onion compresses was 37.98oC and after giving red onion compresses in the first 5 minutes 37.87 oC, at 10 minutes 37.71 oC and at 15 minutes 37.47 oC. There is an effect of giving shallot compresses to decrease body temperature in feverish toddlers in the working area of the Kembaran 1 Health Center with a p-value of 0.0001 (< 0.05). The conclusion is that giving red onion compresses for 15 minutes can reduce the body temperature of toddlers with fever by 0.51oC.